Autoridade do árbitro na arbitragem comercial - Dalbosco, Gustavo Dallazem (2022)
The present essay addresses arbitration, as an adequate method of dispute resolution, with emphasis on the arbitrators' authority in commercial arbitration in Brazil. The evolution of the concept of arbitration jurisdiction in the country, jointly with recent legislative and case-law development, demand attention and study, as they have altered the extent of the arbitrator's practice. Thus, this dissertation aims, initially, to study the historical evolution of arbitration in Brazil and, subsequently, to approach the general aspects of commercial arbitration in the country from the perspective of the arbitrator's role. The matter of the arbitrator's jurisdiction is then analyzed in detail to establish its foundations, as a true source of the role of arbitrators in solving disputes through arbitration in Brazil. Having overcome the issue, an overview of the arbitrator's authority and the cooperation of the Judiciary in the consolidation of arbitration as an effective method of conflict resolution in the country in its role as a tool for social pacification is presented